Amelioration of pool boiling thermal performance in case of using a new hybrid nanofluid. (April 2021) - Kamel, Mohammed Saad; Lezsovits, Ferenc; Abdollahi, Ali; Izadi, Mohsen
Abstract: Unremitting endeavors have been devoted by numerous researchers to ameliorate thermal performance of pool boiling by reducing the superheat temperature value using various approaches. This study aims to experimentally investigate the pool boiling thermal performance of A l 2 O 3 and C e O 2 hybrid nanoparticles with 50:50 mixing ratio based deionized c1 water at atmospheric pressure condition. The pool boiling curves, pool boiling heat transfer coefficient PBHTC enhancement ratio with different dilute volumetric concentrations ranging (0.01–0.1% Vol.) from horizontal typical copper tube were examined. Results demonstrated that the enhancement ratio for hybrid nanofluid was improved compared to DI water, and the higher enhancement ratio was 1.37 for volume concentration of 0.05% Vol at low heat flux. Finally, this type of hybrid nanofluids could remove high heat flux at a small temperature difference, especially with this type of heater geometry, initial surface roughness, nanoparticles type, size, and the volumetric concentration. Highlights: Performance of pool boiling heat transfer of new hybrid nanofluids was experimentally studied. Temperatures distribution along heating surface for DI water and nanofluid at different heat fluxes were discussed. The higher PBHTC enhancement percentage was 37 % for hybrid nanofluids at volume fraction 0.05 % Vol. and moderate heat flux. Heater geometry has an important effect on PBHTC of nanofluids. Introduction.